2018
DOI: 10.1186/s13102-018-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of test loads on the accuracy of 1RM prediction using the load-velocity relationship

Abstract: BackgroundNumerous methods have been proposed that use submaximal loads to predict one repetition maximum (1RM). One common method applies standard linear regression equations to load and average vertical lifting velocity (Vmean) data developed during squat jumps or three bench press throw (BP-T). The main aim of this project was to determine which combination of three submaximal loads during BP-T result in the most accurate prediction of 1RM Smith Machine bench press strength in healthy individuals.MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…While the MV is often recommended to be used when analyzing the load-velocity profile, it has been suggested that when looking at ballistic [ 35 ] or semi-ballistic movements, the use of PV may result in more accurate and reliable predictions of the 1-RM [ 36 ]. In the present study when the entire group was examined, there was no significant difference ( p = 0.367, d = −0.11) between the predicted 1-RM (75.5 ± 12.8 kg) and the criterion measure (76.9 ± 13.0 kg) when PV was used in conjunction with a four-point linear regression analysis ( Figure 1 a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the MV is often recommended to be used when analyzing the load-velocity profile, it has been suggested that when looking at ballistic [ 35 ] or semi-ballistic movements, the use of PV may result in more accurate and reliable predictions of the 1-RM [ 36 ]. In the present study when the entire group was examined, there was no significant difference ( p = 0.367, d = −0.11) between the predicted 1-RM (75.5 ± 12.8 kg) and the criterion measure (76.9 ± 13.0 kg) when PV was used in conjunction with a four-point linear regression analysis ( Figure 1 a).…”
Section: Discussionmentioning
confidence: 99%
“…While some researchers suggest that PV is a more appropriate measure when examining ballistic movements [ 36 , 37 ], like the power clean, an alternative approach is to construct the load-velocity profile using the mean velocity [ 38 ]. García-Ramos et al [ 38 ] have presented data that suggest that MV is the most appropriate variable to monitor during ballistic exercises, such as the bench press throw, performed in a Smith machine.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a simplified two-point version has also been suggested, where 1RM is predicted from two submaximal loads (e.g., 45% and 85% 1RM) [ 17 , 25 ]. Despite differences in the construction of each approach, practically perfect correlations ( r > 0.9), goodness of model fit (R 2 > 0.9), and low systematic bias between direct and predicted 1RM data (<10 kg) have been observed [ 12 , 14 , 17 , 23 , 24 , 26 ]. Whilst these data indicate predictive validity, the studies are limited to isolated, controlled upper body exercises such as the bench press or prone row, rendering the applicability to exercises beyond these unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the well-known load-velocity relationship [8,9,10], for which lighter loads are moved at faster velocities and heavier loads are moved at slower velocities. This method has been applied to numerous exercises, with barbell velocity during the bench press and back squat shown to be highly correlated with relative 1 RM training intensity over a wide range of loads [8,9,10,11,12,13]. Thus, the method for monitoring strength training intensities using barbell velocity is a valid approach to training intensity prescription.…”
Section: Introductionmentioning
confidence: 99%